STUDIES ON INTERFERENCE AMONG TREES IN A PLANTATION OF ALTINGIA EXCELSA - KAN-ICHI SAKAI (BIOTROPIA, 1987)
A  study  was made with  the  use  of  a  50-year  old  Altingia  excelsa Noronha  plantation with  260 standing trees for separating components of density and intraspecific competition. A component of density effect  causes overall decrease  in growth while  that of  competition  results  in a  contrasting  effect  in growth between any pair of neighboring trees. To detect this density effect, it is most appropriate to use an area of ca. 100 m2 irrespective of the experimental area, e.g. circular or quadratic. Competition effect cannot be detected when two individuals are apart more than two meters. An application of the density and competitive ability to tree breeding is briefly mentioned.